Influencer and Viral Marketing: Strengthening Efforts Brand Image on Local Cosmetic Brands Somethinc - Aris Baharuddin; Nur Astaman Putra; Natasya Ananda Lili; Kemal Sandi (PINISI Discretion Review, 2023)
This study aims to describe the formation of the brand image through influencer and viral marketing on the local cosmetic brand Something. Brand image variable indicators include strength, uniqueness, and superiority or preference. The indicators of influencer variables include expertise, trust, and attractiveness. Meanwhile, indicators of viral marketing variables include product knowledge, product information clarity, and product discussion. The research method used is quantitative. The sample used is the sample formulated by Slovin, namely as many as 100 respondents, with data collection techniques through questionnaires. The data obtained were processed using data analysis techniques in the form of validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The results showed that the brand image variable, influencer, and viral marketing partially positive and significant effect on purchasing decisions.